A Longitudinal Follow-Up Study of Saffron Supplementation in Early Age-Related Macular Degeneration: Sustained Benefits to Central Retinal Function. (18th July 2012) - Piccardi, M.; Marangoni, D.; Minnella, A. M.; Savastano, M. C.; Valentini, P.; Ambrosio, L.; Capoluongo, E.; Maccarone, R.; Bisti, S.; Falsini, B.
Abstract : Objectives . In a previous randomized clinical trial (Falsini et al. (2010)), it was shown that short-term Saffron supplementation improves retinal flicker sensitivity in early age-related macular degeneration (AMD). The aim of this study was to evaluate whether the observed functional benefits from Saffron supplementation may extend over a longer follow-up duration. Design . Longitudinal, interventional open-label study. Setting . Outpatient ophthalmology setting. Participants . Twenty-nine early AMD patients (age range: 55–85 years) with a baseline visual acuity >0.3. Intervention . Saffron oral supplementation (20 mg/day) over an average period of treatment of 14 (±2) months. Measurements . Clinical examination and focal-electroretinogram-(fERG-) derived macular (18 ° ) flicker sensitivity estimate (Falsini et al. (2010)) every three months over a followup of 14 (±2) months. Retinal sensitivity, the reciprocal value of the estimated fERG amplitude threshold, was the main outcome measure. Results . After three months of supplementation, mean fERG sensitivity improved by 0.3 log units compared to baseline values (P < 0.01 ), and mean visual acuity improved by two Snellen lines compared to baseline values (0.75 to 0.9, P < 0.01 ). These changes remained stable over the follow-up period. Conclusion . These results indicate that in early AMD Saffron supplementation induces macular function improvements from baseline that are extended over a long-term followup.